PANDANGAN ILMU ADMINISTRASI PUBLIK MENGENAI SIGNIFIKANSI PARTISIPASI MASYARAKAT DALAM PENYELENGGARAAN NEGARA - Hendrikus Triwibawanto Gedeona (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Thare has been a shift of paradigm and practice in state administration from ‘government’ to ‘governance’. The shift has been marked by the recognition of multiactors involved or engaged in state administration, including in the proces of development. It is assumed that good governance can materialize when there are participation, partnership ans positive synergy among thoseactors in managing resources, solving public problems, and encountering other public affairs. Partnership between government and society including private sector deserves a crucial discussion in this context. Thus, citizen’s participation becomes a precondition which is substantial and urgent. By getting involved in the state administration, together with their government and its bureaucacy lines citizens have the responsibility in managing resources, unraveling public problems and tackling other public affairs for the sake of a better state of social well-being.